The last Emperox - Scalzi, John, 1969- (Scalzi, John, 1969- Interdependency, 2020)
"The Last Emperox is the thrilling conclusion to the award-winning, New York Times and USA Today bestselling Interdependency series, an epic space opera adventure from Hugo Award-winning author John Scalzi. The collapse of The Flow, the interstellar pathway between the planets of the Interdependency, has accelerated. Entire star systems--and billions of people--are becoming cut off from the rest of human civilization. This collapse was foretold through scientific prediction . . . and yet, even as the evidence is obvious and insurmountable, many still try to rationalize, delay and profit from, these final days of one of the greatest empires humanity has ever known. Emperox Grayland II has finally wrested control of her empire from those who oppose her and who deny the reality of this collapse. But "control" is a slippery thing, and even as Grayland strives to save as many of her people form impoverished isolation, the forces opposing her rule will make a final, desperate push to topple her from her throne and power, by any means necessary. Grayland and her thinning list of allies must use every tool at their disposal to save themselves, and all of humanity. And yet it may not be enough. Will Grayland become the savior of her civilization . . . or the last emperox to wear the crown?"--Jacket flap.